El Delito de Lavado de Activos y su Aplicación Subsidiaria de Lege Ferenda - Asmat Salazar, Raisa Olenka (2018)
In the present research work we have as an objective do an analysis of the problematic of the CRIME OF MONEY LAUNDERING in Peru, and from the perspective of repression of this illicit by the justice operators, to know what is the current situation and its eventual prospective in the investigation of the crime of laundering of assets in the Fiscal District of La Libertad and in the Judicial District of the Superior Court of Justice of La Libertad, from 2016 to 2017, in order to be able to fight against this criminal offense. This paper we will present statistical data from the Tax District of La Libertad and the Judicial District of the Superior Court of Justice of La Libertad (in the form of tables represented with their respective graphics corresponding emphatically from the year 2016 to 2017). In doctrinal matters, all Peruvian legislation in force was resorted to, in addition to various studies related to money laundering by professionals specialized in the subject. The investigation shows that the crime of money laundering has increased based on the number of investigations initiated in Peru, linked to base crimes known as "crimes of greater social connotation" and, likewise, processes in the Superior Court of Justice of La Libertad, since 2016 and 2017; there are 8 processes in process, 4 processes dismissed, 01 process in intermediate stage, and only 01 process is in trial stage; This is due to the dogmatic, doctrinal and jurisprudential discussion that has been given about the substantive autonomy of the crime in comment. For that reason, we make a criticism of the normative structure of the crime of money laundering, and we determine the creation of a subsidiary type of crime, and in this way, establish our point of view regarding the function and / or nature that fulfills the crime prior to the crime of money laundering, taking into account the arguments outlined both by national and foreign doctrine, as well as the contribution of national and comparative jurisprudence. Considering these considerations, this research work is important and important, because it allows us to know what are the main advances, actions and limitations of the operators of justice, in their fight against money laundering, as part of the public policies of the State. Allowing suggestions for corrections and improvements for the sake of State security